Influence of Academic Supervision and Religious Culture on Learning Achievement through Teacher Motivation - Reza Fathurahman; Siti Djulaikah; Imran Imran; Ilham Ilham; Nurlaili Nurlaili; Haeruddin Haeruddin (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study examines the influence of academic supervision and religious organizational culture on students’ learning achievement, with teachers’ work motivation functioning as a mediating variable. Utilizing a quantitative approach with a causal correlational design, the research was conducted at two public Islamic senior high schools (MAN) in Samarinda, involving 100 teachers selected through proportional random sampling. Data were collected using validated Likert-scale questionnaires and documentation of students’ academic records. Path analysis revealed that both academic supervision and religious organizational culture had significant direct effects on teachers’ work motivation, with religious culture showing the stronger influence. Teachers’ motivation also demonstrated a significant direct effect on students’ learning achievement, indicating that motivated teachers are more likely to implement engaging, effective pedagogical practices. Furthermore, academic supervision and religious organizational culture were found to exert significant indirect effects on student achievement through teachers’ motivation, as confirmed by Sobel testing. These findings highlight the essential role of motivational factors in transforming leadership practices and cultural environments into measurable improvements in learning outcomes. The study concludes that strengthening instructional supervision and cultivating a strong religious organizational culture are strategic steps for enhancing teacher motivation and improving the overall quality of madrasah education